2010
DOI: 10.1002/adsc.200900874
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Oxidative sp2 CH Bond Acylation with Aldehydes

Abstract: An efficient method was developed for the direct acylation of arene sp 2 C À H bonds with aldehydes using palladium acetate as catalyst and peroxide as oxidant. The solvent-free oxidative acylation reaction assisted by a pyridine directing group provides an easy access to aromatic, aliphatic, and optical active ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(61 citation statements)
references
References 36 publications
3
58
0
Order By: Relevance
“…In 2010, Li and co-workers were able to expand the scope of this transformation to include Pd-catalyzed oxidative C–H acylation with alkyl aldehydes with the reaction conducted under neat conditions and employed tert -butyl hydroperoxide (TBHP) as oxidant. 21 …”
Section: Aldehydesmentioning
confidence: 99%
“…In 2010, Li and co-workers were able to expand the scope of this transformation to include Pd-catalyzed oxidative C–H acylation with alkyl aldehydes with the reaction conducted under neat conditions and employed tert -butyl hydroperoxide (TBHP) as oxidant. 21 …”
Section: Aldehydesmentioning
confidence: 99%
“…[2] Since the pioneering discovery of C À H bond activation by Murai, [3] recent progress has been focused on dehydrogenative cross-coupling between sp 2 or sp 3 C À H bonds and sp 2 C À H bonds of arenes or alkenes. [13] Later, palladium-catalyzed sp 2 C À H bond acylations of 2-arylpyridines, [14] oxime, [15] acetanilides, [16] and indole [17] with aldehydes or alcohols were described. Although the reactions using arenes or alkenes as coupling partners have been well documented, the reactions between the aromatic sp 2 C À H bond and aldehydes remain relatively unexplored.…”
mentioning
confidence: 99%
“…However, alkyl aldehydes were not converted. In 2010, Li and co‐workers reported that both aromatic and aliphatic aldehydes could be successfully applied by using tert ‐butyl hydroperoxide (TBHP; 5 M in decane) as the oxidant under neat conditions (Scheme ) 4b. No desired product was obtained in the model system when [Ru 3 CO 12 ] or [Rh(cod)Cl] (cod=1,5‐cyclooctadiene) was applied as the catalyst.…”
Section: Discussionmentioning
confidence: 99%